PWE-196 Factors predicting mortality in acute severe gallstone pancreatitis. (22nd June 2015) - Jenkins, H; Ewan, L; Reddy, Y; Chang, D; Kausar, A; Harris, C; Subar, D; Lapsia, S; Sebastian, D
Abstract : Introduction: The British Society of Gastroenterology (BSG) guidelines state that "Urgent therapeutic ERCP should be performed in patients with acute pancreatitis of suspected or proven gall stone aetiology who satisfy the criteria for predicted or actual severe pancreatitis". The Cochrane review in 2012 suggested that ERCP does not affect morbidity and mortality and some patients with gallstones in the CBD will pass spontaneously. Aim: The aim of this study was to assess predictive factors of mortality and the need for ERCP in severe gallstone pancreatitis. Method: Data for patients who presented with acute severe biliary pancreatitis between January 2012 and April 2014 was collected. Data collected included predicted severity (Modified Glasgow score), liver function tests, white cell count, USS, ERCP and MRCP reports. Overall 90 day mortality was also recorded. Results: 123 patients had predicted severe pancreatitis. On US 21 patients had a dilated CBD and 16 had CBD stone. 51% of patients (n = 63) had MRCP of which 22 patients had CBD stones. 60 patients had ERCP. In 17% (n = 21) no stone was found. 2 patients (3%) developed post ERCP pancreatitis.11% (n = 14)of the patients admitted with predicted severe acute pancreatitis died. On univariate analysis albumin (p = 0.003), alanine transaminase (ALT) (p= <0.05) but not ERCP was significant in predicting mortality. High white cell count demonstrated a trend towards predicting mortality (p = 0.08) but did not reach statistical significance. On multivariate analysis albumin (p = 0.41) and ALT (p = 0.005) retained statistical significance. Conclusion: Low serum albumin and ALT predicts mortality in severe GSP but ERCP does not and may precipitate further attacks of pancreatitis. Patients who have severe gallstone pancreatitis without deteriorating LFTs or cholangitis should have an MRCP to confirm stones in the CBD prior to ERCP. Disclosure of interest: None Declared.